رؤية اللغة في الذات والحركة - وقاف حسين حبيب (Latakia University Journal - Arts and Humanities Sciences Series, 2013)
يدرس هذا البحث النظرية اللغوية من خلال خصائص اللغة العربية، ويبحث في القوانين التي يمكن أن تُلمس في متن اللغة، وتقدم رؤية للوجود، تتفرد عما سواها من طروحات الفكر اللغوي، وهو يلقي الضوء في ثنايا البحث على ثوابت الوجود العقلية، ويربط بينها وبين الاستدلال اللغوي، ويسلك في تتبعه للظواهر اللغوية مسلك تحليل المتن اللغوي من زاوية ترى اللغة مظهراً من مظاهر الوجود الحسي، تنطبع فيه النواميس المجردة لسلوك الأشياء، وبالتالي يحاول إثبات الصلة المباشرة بين اللغة كظاهرة إنسانية، و القوانين العقلية من جهة، وبينها وبين قوانين المادة من جهة أخرى، غائصاً في أثناء ذلك في جماليات اللغة العربية. This research studies the linguistic theory throughout Arabic Language characteristics and laws which could be Found in structure of language. It also draws attention to the constituents of the mental existence, and connects them with the linguistic deduction. This study discusses the linguistic phenomena, and analyzes the linguistic structure in the same way wherefrom we can see the language as sensual existence phenomenon overlapping with abstract lawsof thebehavior of things.Subsequently, this study tries to confirm the relevance, on theone hand, between the language as a human phenomenon and the mental laws. On the other hand, it relates to the language and the material laws bringing out the beauty of the Arabic language.